Pengembangan Jejaring Wirausaha dan Pembelajaran Eksploratif Sebagai Upaya Meningkatkan Kinerja Perekonomian Unit Usaha Kecil Menengah di Semarang - Enny Susilowati M; Guruh Taufan (Semantik, 2013)
The research examines the effect Network of Entrepreneurial which measured by social networking, networking support, networking among firms and Explorative Learning toward Performance Unit Small and Medium Enterprises in Semarang.This research use sample consisted of 100 Unit Small and Medium Enterprises in Semarang. The data are taken from central statistical agency of Semarang. Selection of samples by using purposive sampling. The hypothesis testing model using Partial Least Square analysis (PLS. The result of the research indicated, the Network of Entrepreneurial and Explorative Learning are factors that affect positively on Performance Unit Small and Medium Enterprises . The positive result in Network of Entrepreneurial and Explorative Learning gives the impact for Unit Small and Medium Enterprises in Indonesia to more focus Network of Entrepreneurial Development Model. These findings contribute that entrepreneurial networking should be astrategic priority for every company. Linkages with suppliers to increase the resources of the market development, new technologies and competitors movement and access to business partners, sources of technical assistance from customer ideas. With the existence of a positive relationship between Entrepreneurial Networking and Explorative Learning is a key factor in developing the dissemination of knowledge and learning that will increase competitive advantage and improve the performance of SMEs.